Urogenital Malignancy and Cannabis Use: A Narrative Review - Alice Thomson; Aoife McVey; Brennan Timm; Damien Bolton (Société Internationale d’Urologie Journal)
BackgroundCannabis is the most commonly used illicit drug worldwide. An increasing number of jurisdictions are legalising cannabis for both medicinal and recreational use. The changing cannabis market has resulted in both an increase in the number of people consuming these compounds, and an increase in the frequency and quantity of cannabis being used. Endogenous and exogenous cannabinoids act on receptors across the entire body including the genitourinary system; however, there is a paucity of understanding of how cannabinoids affect genitourinary malignancy. ObjectiveTo present a narrative review of the available literature detailing the relationship between cannabis and the incidence, diagnosis, and management of genitourinary malignancy. MethodsA comprehensive search was undertaken using the Ovid MEDLINE, Ovid Embase, and Cochrane Central Register of Controlled Trials (CENTRAL) up to July 2021. Studies included case reports, case series, case-control studies, and in vitro studies. ResultsThe search identified 40 studies in total: 8 described the relationship between cannabis and testicular carcinoma, 20 related to prostate cancer, 5 to bladder cancer, 5 to renal cancer, 1 to penile cancer, and 1 study examined testicular carcinoma, renal cell carcinoma, bladder cancer, and prostate cancer. ConclusionsCannabis use has been linked to an increased risk of developing testicular tumours, whilst the evidence for bladder cancer is mixed. There is no apparent increase in risk for prostate cancer, penile cancer, or renal cell carcinoma; however, this evidence was based on a very small number of patients. There remains a lack of understanding of the relationship between cannabis and genitourinary malignancy. With an expected increase in cannabis use, monitoring for testicular tumour plus efforts to further understand its effects upon the genitourinary tract will aid diagnosis and management.